Characterization of hydroxytyrosol-β-cyclodextrin complexes in solution and in the solid state, a potential bioactive ingredient. (March 2019) - Malapert, Aurélia; Reboul, Emmanuelle; Tourbin, Mallorie; Dangles, Olivier; Thiéry, Alain; Ziarelli, Fabio; Tomao, Valérie
Abstract: This study focused for the first time on characterizing the inclusion complexes between β-cyclodextrin (β-CD) and hydroxytyrosol (HT) in the solid state. In solution, HT and β-CD are able to form a 1:1 inclusion complex with an association constant of 33.2 ± 3.7 M -1 . In the solid state, the inclusion complexes prepared by freeze-drying and spray-drying of an equimolar mixture of both partners were characterized and compared by 13 C NMR and SEM. After dissolution, their free radical-scavenging ability was also determined by UV–visible spectroscopy. The results show that β-CD and drying processes have no effect on the efficiency of HT to reduce the DPPH radical. The solid state 13 C NMR data provided information on the spatial proximity between β-CD and HT and suggest the formation of inclusion complexes for both drying processes compared to the physical mix. However, the morphology of the solids obtained was significantly different, as spherical particles were formed by spray-drying while freeze-drying only provided irregular shapes. Highlights: Freeze- and spray-drying processes are compared for inclusion in the solid state. Solid state NMR provides structural information on the β-CD – HT binding. SEM shows distinct outer structures for the complexes obtained by drying.